Le certificat fédéral de capacité en Suisse – Quelles significations sociales pour un diplôme hétérogène ? - Sasha Cortesi; Christian Imdorf (Cahiers de la Recherche sur l'Education et les Savoirs)
Switzerland stands out from the panorama of Vocational education and training (VET) in Europe due to its heterogeneous education system. A compromise between different educational logics is implemented in the consensus around the most important VET certificate. Focusing on the Federal VET diploma evokes the singularity of the Swiss case that offers a true laboratory of educational VET policies. Following the institutional and socio-historical reconstruction of the landscape of VET, this paper focuses on the heterogeneities of the vocational degree par excellence in Switzerland. However, the consensus around the Federal VET Diploma hides a number of major sociological issues, which will be outlined in the last part of the article. Academic differentiation and social reproduction, social selectivity, social hierarchy and segregation might be all hidden facets of the same institutional reality that seems immaculate at first glance.